National quality improvement programmes need time and resources to have an impact. (9th October 2019) - Cook, Rob; Lamont, Tara; Martin, Rosie
The study: Peden CJ, Stephens T, Martin G et al. Effectiveness of a national quality improvement programme to improve survival after emergency abdominal surgery (EPOCH): a stepped-wedge cluster-randomised trial. Lancet 2019;393:2213-21. This project was funded by the NIHR Health Services and Delivery Research Programme (project number 12/5005/10). To read the full NIHR Signal, go to https://discover.dc.nihr.ac.uk/content/signal-000789/national-quality-improvement-programmes-need-time-and-resources-to-have-impact